2012
DOI: 10.1186/1756-3305-5-294
|View full text |Cite
|
Sign up to set email alerts
|

Circumstantial evidence for an increase in the total number and activity of borrelia-infected ixodes ricinus in the Netherlands

Abstract: BackgroundBetween 1994 and 2009, a threefold increase has been observed in consultations of general practitioners for tick bites and Lyme disease in The Netherlands. The objective of this study was to determine whether an increase in the number of questing ticks infected with B. burgdorferi sensu lato is a potential cause of the rise in Lyme disease incidence.MethodsHistoric data on land usage, temperature and wildlife populations were collected and analyzed together with data from two longitudinal field studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 53 publications
4
64
3
1
Order By: Relevance
“…Our findings are in contrast to previous studies that showed a linear relationship 38,39 or a parabolic relationship 205 between deer density and I. ricinus density. This difference could be due to differences in host assemblage composition between different studies.…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…Our findings are in contrast to previous studies that showed a linear relationship 38,39 or a parabolic relationship 205 between deer density and I. ricinus density. This difference could be due to differences in host assemblage composition between different studies.…”
Section: Discussioncontrasting
confidence: 56%
“…This, together with a large distribution in suitable habitat and climatic conditions, explains why I. ricinus has such a wide distribution, and why it occurs in high densities in many areas with a vertebrate assemblage existing of widespread species. It also supports the hypothesis that the increase in Lyme borreliosis may be due to an increase in I. ricinus distribution and abundance 39,61 , following increases in range and abundance of widespread host species such as Bank vole, Blackbird and Roe deer [147][148][149] .…”
Section: Importance Of Host Species In Maintaining I Ricinussupporting
confidence: 58%
See 3 more Smart Citations